Methodology for Selection of Agile Practices - Saleh, Majd H. (2013)
A Master of Science thesis in Computer Engineering by Majd H. Saleh entitled, "Methodology for Selection of Agile Practices," submitted in June 2013. Thesis advisor is Dr. Armin Eberlein and Co-advisor is Dr. Michel Pasquier. Available are both soft and hard copies of the thesis.